Long-term longitudinal evalutation of mandibular growth in patients with Beckwith-Wiedemann Syndrome treated and not treated with glossectomy. Issue 12 (December 2020) - Meazzini, Maria Costanza; Besana, Melissa; Tortora, Chiara; Cohen, Noah; Rezzonico, Angela; Ferrari, Mario; Autelitano, Luca
Abstract: Aim: This study compares long-term mandibular growth between a group of Beckwith-Wiedemann Syndrome (BWS) patients who underwent glossectomy at an early age and a group of patients not operated. Methods: Cephalometric measurements were performed in BWS patients comparing the data obtained between a group of patients operated at an early age and a group of non-operated patients who declined surgery. Statistics included independent sample T-test. Results: Twenty-four out of 78 BWS patients followed since birth completed longitudinal cephalometric x-rays at age 5, 10 and 15. Eighteen patients needed early surgery. Eleven families accepted glossectomy at 2.3 ± 1.3 years of age; seven declined surgery. No differences in mandibular growth were found between the two groups. Inclination of maxillary incisors results were statistically greater in the non-operated group (operated compared to the non-operated group: 103.58 ± 11.30 Vs 108.98 ± 12.47; p-value 0.0168 at 5; 107.06 ± 7.98 Vs 115.14 ± 7.05; p-value 0.0206 at 10; 109.80 ± 4.68 Vs 116.75 ± 5.28; p-value 0.0233 at 15). Conclusion: Macroglossia has no role in the post-natal mandibular overgrowth in BWS and mandibular overgrowth is part of the syndrome. Therefore, early glossectomy does not change mandibular growth and does not prevent the development of class III skeletal malocclusion in these patients.